2021
DOI: 10.1186/s13041-021-00792-9
|View full text |Cite
|
Sign up to set email alerts
|

Loss of park7 activity has differential effects on expression of iron responsive element (IRE) gene sets in the brain transcriptome in a zebrafish model of Parkinson’s disease

Abstract: Mutation of the gene PARK7 (DJ1) causes monogenic autosomal recessive Parkinson’s disease (PD) in humans. Subsequent alterations of PARK7 protein function lead to mitochondrial dysfunction, a major element in PD pathology. Homozygous mutants for the PARK7-orthologous genes in zebrafish, park7, show changes to gene expression in the oxidative phosphorylation pathway, supporting that disruption of energy production is a key feature of neurodegeneration in PD. Iron is critical for normal mitochondrial function, a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Mitochondrial membrane potential is also reduced in DJ-1 knockout mouse embryonic fibroblasts [34]. Analysis of transcriptome data from park7−/− zebrafish brains suggests that mitochondrial oxidative stress and iron dyshomeostasis comprise early preclinical events in PD [36].…”
Section: Role In Mitochondrial Functionmentioning
confidence: 99%
“…Mitochondrial membrane potential is also reduced in DJ-1 knockout mouse embryonic fibroblasts [34]. Analysis of transcriptome data from park7−/− zebrafish brains suggests that mitochondrial oxidative stress and iron dyshomeostasis comprise early preclinical events in PD [36].…”
Section: Role In Mitochondrial Functionmentioning
confidence: 99%
“…Park7 is expressed ubiquitously and was originally identified in dopaminergic neurons of familial Parkinson's disease patients. [18] Chin et al observed altered IRE gene transcript abundance in Park7 knockout zebrafish brain [43] and Lin et al reported a novel PARK7 homozygous mutation (c.390delA) responsible for autosomal recessive early-onset Parkinson Disease. [44] Loss of myocardial Park7 protein has been observed in end-stage heart failure patients [19] and Park7 knockout mice were more vulnerable to myocardial infarction and pressure overload challenges.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of zebrafish, single depletion of Pink1 is sufficient to induce the loss of dopaminergic neurons [99][100][101]. DJ-1 knockout zebrafish and medaka models have also been created, which need further pathological evaluations but are promising for the production of new fish models of Parkinson's disease [102][103][104][105].…”
Section: Zebrafish and Medaka Models Of Parkinson's Diseasementioning
confidence: 99%